A shortened surface electromyography recording is sufficient to facilitate home fasciculation assessment. Issue 5 (2nd September 2022) - Crook‐Rumsey, Mark; Musa, Abdi Malik; Iniesta, Raquel; Drakakis, Emmanuel; Boutelle, Martyn G.; Shaw, Christopher E.; Bashford, James
Abstract: Introduction/Aims: Fasciculations are an early clinical hallmark of amyotrophic lateral sclerosis (ALS), amenable to detection by high‐density surface electromyography (HDSEMG). In conjunction with the Surface Potential Quantification Engine (SPiQE), HDSEMG offers improved spatial resolution for the analysis of fasciculations. This study aims to establish an optimal recording duration to enable longitudinal remote monitoring in the home. Methods: Twenty patients with ALS and five patients with benign fasciculation syndrome (BFS) underwent serial 30 min HDSEMG recordings from biceps brachii and gastrocnemii. SPiQE was independently applied to abbreviated epochs within each 30‐min recording (0–5, 0–10, 0–15, 0–20, and 0–25 min), outputting fasciculation frequency, amplitude median and amplitude interquartile range. Bland–Altman plots and intraclass correlation coefficients (ICC) were used to assess agreement with the validated 30‐min recording. Results: In total, 506 full recordings were included. The 5 min recordings demonstrated diverse and relatively poor agreement with the 30 min baselines across all parameters, muscles and patient groups (ICC = 0.32–0.86). The 15‐min recordings provided more acceptable and stable agreement (ICC = 0.78–0.98), which did not substantially improve in longer recordings. Discussion: For the detection and quantification of fasciculations in patients with ALS and BFS, HDSEMG recordings can be halved from 30 to 15 min without significantly compromising the primary outputs. Reliance on a shorter recording duration should lead to improved tolerability and repeatability among patients, facilitating longitudinal remote monitoring in patients' homes.